Quality of school life of adolescents in Finland and Korea: a cross-cultural and comparative study - Yoon, Junghyun (fi=Turun yliopisto|en=University of Turku|, 2020)
This study explores the quality of school life of Finnish and Korean adolescents. First, it investigates adolescents’ perceptions of their quality of school life by identifying the crucial aspects of quality of school life (general satisfaction, peer relations, and teacher-student relations). Thereafter, a more in-depth exploration of these crucial aspects of quality of school life are explored by focusing on students’ peer relations as well as tensions and negotiations that occur between student agency and school control. This study also illuminates how student agency is controlled or manifested in students’ interactions with teachers and how students reflect their experiences with control and agency in daily school life. The theoretical approach of this study departs from the concept of quality of school life. I utilise Foucault’s ([1975] 2003; 1984) and Butler’s thoughts (1988; [1990] 2008) as well as Bernstein’s theory of classification and framing (1996) to discuss control and agency. In addition, I employ cross-cultural and comparative studies as methodological approaches and discuss the notions, benefits, and dilemmas associated with as well as the objectives fulfilled by cross-cultural and comparative studies. Further, this thesis was conducted using a mixed-methods design. The quantitative data was collected from student survey items taken from PISA 2012 studies, targeting 15-year-old Finnish and Korean students (study 1). The qualitative data was produced from fieldwork inspired by an ethnographic approach, in two comprehensive schools in southern Finland and two primary and two lower-secondary schools in Seoul, Korea. The qualitative data consists of field notes generated through observations and interviews with students (grades 6, 8, and 9) and their class teachers (studies 2 and 3). The findings of the quantitative study revealed that, in all the dimensions of quality of school life (general satisfaction, peer relations, and teacher-student relations), both Finnish and Korean adolescents’ perceptions were less affirmative compared with those of students in other OECD countries on average. Further, the perceptions of Finnish and Korean students, compared to the OECD average, were the least positive for teacher-student relations. In the first two dimensions, Finnish adolescents’ views appeared to be more positive than that of Korean students. Subsequently, qualitative findings elaborated that young people strived for two demanding tasks of school life: studying and friends. Many students—regardless of their school grade, gender, and socioeconomic status—perceived the importance of high achievement or at least of accomplishing school work, with regard to their future path and career. Simultaneously, students found meaning in attending school from the relationships with their friends. Their peer relations connoted emotional support as well as hierarchy and conflict for both genders. The students constructed gendered identities through the patterns of their peer relations, and gender roles were constructed in school scenes organised by adults. Students displayed diverse patterns of peer interactions, moving between independence and interdependence, and these patterns appeared somewhat differently in the Finnish and Korean schools. However, an academically competitive spirit among peers did not distinctly appear among either the Finnish or Korean students. Further, in all the Finnish and Korean schools studied, student agency was tightly controlled by the regulations of time, space, and movement and was extensively limited in teaching-learning practices. Some teachers, who appeared to exercise weak control on student conduct and their use of time and space, exercised strong control over the sequence and contents of lessons, teaching-learning methods, and evaluation criteria. Many students appeared to be accustomed to strong control in teaching-learning practices, and some students did not welcome teachers’ weak control in instruction methods that attempted to encourage students’ agency and active participation. Moreover, variations of control and agency were observed in student-teacher interactions in daily routines. A less vertical relationship and rather weak teacher control over students’ self-expression (e.g., appearance and the use of smartphones in school) were observed in the Finnish schools, whereas a hierarchical relationship and class teachers’ intensive control and care work were more noticeable in the Korean schools. This study interprets that historical, sociocultural, and institutional contexts are linked with the roles of schoolteachers and students and also with students’ views and experiences of their quality of school life. I argue that more aspects of a disciplinary school were visible in the Korean schools, whereas the Finnish schools seemed to be shifting slightly ahead towards being schools of self-regulating learners. However, the symptom of self-responsible learner identity was visible in both the Finnish and Korean schools, including students who were considered as intractable and low-achieving. Their attitudes were somewhat different from the studying-diminishing manners that adolescents from disadvantaged social backgrounds revealed in the ethnographic studies conducted in previous years. Lastly, this thesis conveys a message of democratic school culture in terms of the quality of school life.

Tutkimuksen kohteena on nuorten kouluelämän laatu Suomessa ja Koreassa. Ensinnäkin tutkimus selvittää nuorten kouluelämän laatua koskevia käsityksiä tunnistamalla siihen liittyviä keskeisiä tekijöitä (yleinen tyytyväisyys, vertaissuhteet sekä opettaja-oppilas -suhteet). Tämän jälkeen näitä tutkitaan tarkemmin pureutumalla oppilaiden vertaissuhteisiin sekä niihin jännitteisiin ja neuvottelustrategioihin, joita oppilaiden toimijuuden ja koulun kontrollin välillä ilmenee. Tutkimuksessa tarkastellaan myös, miten oppilaan toimijuutta kontrolloidaan tai miten se ilmenee oppilaiden ja opettajien välisessä vuorovaikutuksessa, ja mitä oppilaat itse ajattelevat päivittäisessä kouluelämässä ilmenevistä kontrolliin ja toimijuuteen liittyvistä kokemuksista. Teoreettisesti tutkimus lähtee liikkeelle kouluelämän laadun käsitteestä. Työ hyödyntää myös Foucault’n ([1975] 2003; 1984) ja Butlerin ajattelua (1988; [1990] 2008) sekä Bernsteinin luokittelua ja kehystämistä käsittelevää teoriaa (1996) käsitellessään kontrollia ja toimijuutta. Tämän ohella tutkimus hyödyntää kulttuurienvälisiä ja vertailevia tutkimuksia menetelmällisinä lähestymistapoinaan ja ottaa osaa kulttuurienvälisten ja vertailevien tutkimusten käsitteitä, hyötyjä, dilemmoja ja tehtävää käsittelevään keskusteluun. Työ toteutettiin monimenetelmällisesti. Määrällinen aineisto koottiin PISA 2012 -tutkimuksen oppilastutkimusosiosta, jonka kohteena ovat 15-vuotiaat suomalais- ja korealaisoppilaat (tutkimus 1). Laadullinen aineisto luotiin etnografisen lähestymistavan inspiroimalla kenttätyöllä kahdessa eteläsuomalaisessa peruskoulussa sekä kahdella ala-asteella ja kahdella yläasteella Soulissa, Koreassa. Laadullinen aineisto koostuu kenttämuistiinpanoista, jotka ovat syntyneet havainnoista ja oppilaiden (luokka-asteet 6, 8 ja 9) sekä opettajien haastatteluista (tutkimukset 2 ja 3). Määrällinen tutkimus paljasti, että kaikissa kouluelämän laadun ulottuvuuksissa (yleinen tyytyväisyys, vertaissuhteet sekä opettaja-oppilas -suhteet) sekä suomalaisten että korealaisten nuorten käsitykset olivat vähemmän myönteisiä verrattuna muiden OECD-maiden keskiarvoon. Tämän ohella OECD-keskiarvoon verrattuna suomalaisten ja korealaisten oppilaiden käsitys opettaja-oppilas -suhteista oli kaikkein vähiten positiivinen. Kahdessa ensimmäisessä ulottuvuudessa suomalaisnuorten käsitykset vaikuttivat olevan positiivisempia kuin korealaisoppilaiden. Laadulliset havainnot täsmensivät, että nuoret tekevät töitä kahden vaativan kouluelämää koskevan asian eteen: opiskelun ja ystävien. Riippumatta luokka asteesta, sukupuolesta tai sosioekonomisesta asemasta suurin osa oppilaista koki yhteyden yhtäältä tulevaisuuden polkujensa ja työuriensa sekä toisaalta hyvien koulusuoritusten tai ainakin koulutehtävien läpäisemisen välillä. Samanaikaisesti oppilaat löysivät koulunkäynnin merkityksen ystävyyssuhteistaan. Molemmille sukupuolille vertaissuhteet merkitsivät paitsi henkistä tukea myös hierarkioita ja konflikteja. Sukupuoli-identiteetit rakennettiin vertaissuhteissa. Sukupuolirooleja neuvoteltiin aikuisten järjestämässä päivittäisessä kouluelämässä. Oppilaat osoittivat monimuotoisia itsenäisyyden ja keskinäisriippuvuuden välille asettuvia vertaissuhde-vuorovaikutuskaavoja, jotka näyttäytyivät hieman erilaisina suomalaisissa ja korealaisissa kouluissa. Akateemisesti kilpailuhenkistä ilmapiiriä vertaisten välillä ei noussut esiin sen paremmin suomalaisten kuin korealaistenkaan oppilaiden keskuudessa. Kaikissa suomalaisissa ja korealaisissa kouluissa oppilaiden toimijuutta kontrolloitiin tiukasti ajan- sekä tilankäytön ja liikkumisen rajoitusten kautta, ja liikkumista rajoitettiin merkittävästi opetus- ja oppimiskäytänteissä. Jotkut oppilaiden käytöstä sekä heidän ajan- ja tilankäyttöään vähäisesti kontrolloivat opettajat kontrolloivat kuitenkin tiukasti oppituntien järjestystä ja sisältöä, opetus- ja oppimismenetelmiä sekä arviointikriteereitä. Monet oppilaat vaikuttivat olevan tottuneita tiukkaan kontrolliin opetus- ja oppimiskäytänteiden kohdalla, ja jotkut oppilaat eivät katsoneet hyvällä opettajien opetusmenetelmiä koskevaa heikkoa kontrollia, jonka tehtävänä oli rohkaista oppilaiden toimijuutta ja aktiivista osallistumista. Tämän ohella kontrollin ja toimijuuden muunnelmia havaittiin oppilaiden ja opettajien välisissä päivittäisissä vuorovaikutustilanteissa. Suomalaisissa kouluissa havaittiin vähemmän hierarkkinen suhde sekä vähemmän oppilaiden itseilmaisuun kohdistuvaa kontrollia (esim. ulkonäkö ja älypuhelinten käyttö)opettajien toimesta, kun taas hierarkkinen suhde, intensiivinen kontrolli sekä luokanopettajien muu kasvatustyö olivat selvemmin näkyvissä korealaisissa kouluissa. Tässä tutkimuksessa esitetyn tulkinnan mukaan historialliset, sosiokulttuurilliset sekä institutionaaliset kontekstit ovat yhteydessä opettajien ja oppilaiden rooliin sekä oppilaiden näkemyksiin ja kokemuksiin koskien heidän kouluelämänsä laatua. Korealaisissa kouluissa kurinpidollisen koulun piirteitä oli esillä enemmän, kun taasen suomalaiset koulut vaikuttivat olevan hieman lähempänä itse itseään sääntelevien oppijoiden koulua. Itsevastuullisen oppijan identiteetti oli kuitenkin näkyvissä kaikissa kouluissa, myös uppiniskaisina ja huonosti menestyvinä pidettyjen oppilaiden kohdalla. Heidän asenteensa olivat jossain määrin erilaisia niihin koulukielteisiin asenteisiin nähden, joita huono-osaisista sosiaalisista taustoista tulevat nuoret ovat tuoneet esille aiemmin tehdyissä kouluetnografioissa. Lopuksi tutkimus haluaa korostaa kouluelämän laatuun tähtäävän demokraattisen koulukulttuurin tärkeää merkitystä.